Exploration of Building Information Modeling and Integrated Project Cloud Service in early architectural design stages - Felicia Wagiri; Shen-Guan Shih; Kevin Harsono; Tsung-Wei Cheng; Mu-Kuan Lu (Vitruvio: International Journal of Architectural Technology and Sustainability)
In the evolving Architecture, Engineering, and Construction (AEC) industry, the use of Building Information Modeling (BIM) and Integrated Project Cloud Service (IPCS) has become crucial. These tools are particularly essential during the early design stages, as they enable comprehensive management and integration of project information, thus promoting effective decision-making throughout project lifecycles. This combined approach enhances inter-organizational collaborations, improves design and construction practices, and creates a communal data platform for stakeholders. This research explores the effectiveness of the BIM-IPCS system in streamlining data exchange and information flow during early design, suggesting ways to minimize errors, speed up processes, and reduce construction costs through dependable networks. Conclusively, this study underscores the significant impact of the BIM-IPCS system on project management, ensuring well-coordinated and informed construction while advocating for its role in driving innovative and efficient project delivery in the AEC industry.